The Planning Process - Planning Commission (Planning Commission, 1963)
This paper attempts briefly to describe the approach and methods which have come to be developed in India over the past decade or more. The need for such a document has been felt for some time by students of planning in India and elsewhere. This paper was initially compiled by Shri Tarlok Singh, Member, Planning Commission, as member of an Expert Group set up by the United Nations to prepare a study summarising the experience gained and the techniques in use in the planning of economic development by different countries. Members of the Group, who were drawn from ten different countries, prepared reports on the basis of an agreed outline on the methods and techniques which had been evolved in their respective countries. The Report of the Group on Planning for Economic Development was presented by the Secretary-General to the eighteenth session of the General Assembly in October 1963. Studies of national planning experience prepared by members of the Group as well as studies of other countries prepared at the request of the United Nations arc also being published as Volume II of the Group’s Report.
Government of India Planning Commission